IMPACT OF SOCIO-ECONOMIC CONDITIONS ON INVESTORS’ PERCEPTION TOWARDS MUTUAL FUND INVESTMENT – A STUDY WITH SPECIAL REFERENCE TO VIRUDHUNAGAR DISTRICT - PANDIAN, S. KULOTHUNGA (IJRDO - Journal of Business Management, 2017)
Mutual fund is more profitable investment in the financial market. There is an increasing trend in investing mutual fund in recent decades. Investors showing their interest in investing mutual fund but they have different perception towards mutual fund investment. Each and every investor differs in their style. Various factors influencing the investors’ perception about mutual fund investment while investing their money. The researcher made an attempt to analyse the socio-economic conditions influencing investors’ perception towards mutual fund investment in the study area of Virudhunagar district